COMBINATION OF USING COW FECES POWDER AND PROBIOTIC IN FEED FOR LAYER NATIVE CHICKEN - Guntoro, Suprio; Dinata, Anak Agung Ngurah Badung Sarmuda; Sudarma, I Wayan (Jurnal Biologi Udayana, 2016)
The development of free-range chicken farm is constrained by expensive food prices. On the other hand,feses of cattle had potential use as a source of feed. This study was conducted to determine the response ofcow feses and probiotics administration in the diet of laying range chicken. The study was conducted over 6months using 240 free-range chickens aged 8 months. Research was arranged in a completely randomized designwith 8 treatments and 5 replications. The treatment given were ration in accordance with the farmers formulacomprising: concentrate: 25%, corn 40% and rice bran 35% (P0) and ration as P0, with the substitution of ricebran with fermented cow feses each treatment with level 10 % (P1), 15% (P2) and 20% (P3) and ration as atP0, P1, P2 and P3 that received additional probiotic (Bio L) 1 cc / L of drinking water (P4, P5, P6 and P7). Theparameters were observed are: egg production (hen day), egg weight, feed intake, FCR (Feed Conversion Ratio)mortality and physical composition of eggs. The results showed that the diet which containing fermented cowfeses 20% did not decreased egg production and feed efficiency. The combination of fermented cow feses at thelevel of 20% with a probiotic (Bio L) 1 cc / L of drinking water showed that egg production  increased althoughit is not significant and reduce the number of FCR (Feed Conversion Ratio). In conclusion the use of fermentedcow feses up to the level of 20% in the diet both with and without the administration of probiotics, has no effecton physical composition of eggs.
Keywords: cow feces, free-range chicken, eggs